(untitled) (Western Journal of Medical and Biomedical Sciences, 2025)
Vitamin D is a group of fat-soluble vitamins, commonly known for its critical role in calcium homeostasis and bone mineralization, but more recently it has been implicated in the pathogenesis of hematological cancers and shows promise as an anti-cancer therapy. Serum Vitamin D level has a positive relation with rate of disease progression in Chronic Lymphocytic Leukemia (CLL) and as such Vitamin D deficiency is a poor prognostic factor. This study is designed to evaluate the serum vitamin D concentration in CLL participants in comparison to age-matched non CLL participants. This was a cross-sectional study carried out among CLL patients seeking care in Benue state University Teaching Hospital. Thirty-six CLL patients and 36 healthy age and sex matched controls were recruited for the study. Their Full Blood Count and serum vitamin D levels were determined. Data obtained from the study were analysed using Statistical Package for Social Sciences (SPSS) version 23.0. The concentration of serum vitamin D in the CLL group was significantly lower than that of control. Prevalence of vitamin D deficiency was commoner in the CLL group (52.8%, n=19) compared to controls (5.6%, n=2), P <0.05. There was no correlation between serum Vitamin D and age, Rai stage, neutrophil count, lymphocyte count and haematocrit. However, a negative correlation was found between serum vitamin D and platelet count.There is a high prevalence of Vitamin D deficiency among CLL patients in Makurdi, Benue state. Though this deficiency does not correlate with the Rai stage of the disease. Therefore, serum vitamin D assay should be part of routine investigation done at diagnosis of CLL so that its deficiency can be corrected early.